Digital Platform, Financial Literacy and Motivation on Generation Z's Decision to Invest in Islamic Stocks: A Structural Equation Modelling Analysis - Any Tsalasatul Fitriyah; Naili Rahmawati (IAIN Salatiga, 2022)
This study aims to determine the relationship between the measurement and structural models of digital platform, financial literacy, motivation, and Generation Z's decision to invest in Islamic stocks. Furthermore, this study uses Structural Equation Modeling (SEM) analysis and involves more than two variables, with 123 respondents from West Nusa Tenggara, Indonesia, who actively invest in Islamic stocks, providing accurate information through multivariate analysis. The study found that digital platforms and motivation have a significant impact on Generation Z's decision to invest in Islamic stocks, while financial literacy has an insignificant effect. However, the analysis results indicated that financial literacy has indirectly motivated them to invest in these types of stocks through motivation. This suggests that digital platforms and motivation play a crucial role in investment decisions. Therefore, service providers need to continuously develop digital applications as transaction tools to cater to the needs of Generation Z. Additionally, improving financial literacy is crucial to increasing people's investment skills, even though it may not directly affect investment decisions.